Architecture, Materiality and Society
XIII, 255 p.
Keywords: This book examines the extent to which the insights of STS can be used to analyse the role of architecture in and for social life. The contributions examine the question of whether architecture and thus materiality as a whole has agency. The book also proposes a theoretical and methodological approach on how to research architecture's agency.